Gulf Sustainable Urbanism - Past, Volume II - Spiro N. Pollalis1, Nader Ardalan (Hamad Bin Khalifa University Press, 2018)
The Harvard University Graduate School of Design has been leading a research project entitled Gulf Sustainable Urbanism (GSU) since 2011. This holistic, multi-year, cross-disciplinary, cross-border study focusing on sustainable urbanism in the Gulf Region is sponsored by Msheireb Properties, a subsidiary of Qatar Foundation, Qatar. The main focus of the commissioned research is the future of urbanism in the coastal region, on a sustainable basis, both environmentally and socio- economically. A study of historical urbanization patterns was conducted on a representative sample of 14 urban settlements in 8 countries surrounding the Gulf: twelve coastal cities (including two cases of "twin" cities) and two associated hinterland cities. Urban and regional histories were documented and analyzed to understand the complex relationships that generated long-lasting urban forms and efficient building designs.